LCR and AFD of decode-and-forward relay networks with Nth best relay selection schemes in rayleigh fading channels - Ting, See Ho. (2013)
The second-order statistics are of significance for the design of wireless relay networks. In this correspondence, we have theoretically derived the second-order statistics, level crossing rate (LCR) and average fade duration (AFD), of the Nth best proactive and reactive decode-and-forward (DaF) relaying schemes in Rayleigh fading channels. The above two schemes choose different relaying nodes to assist the signal transmission. It is shown that the theoretically derived LCR and AFD performances match the simulation results. It is also shown that for the Nth best DaF relaying, both proactive and reactive schemes have the same LCR and AFD performances.